1999
DOI: 10.1128/jb.181.14.4374-4380.1999
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of the cbb Operon (CO 2 Assimilation) Promoter of Ralstonia eutropha

Abstract: PL promoters direct the transcription of the duplicatedcbb operons from the facultative chemoautotrophRalstonia eutropha H16. The operons encode most enzymes of the Calvin-Benson-Bassham carbon reduction cycle required for CO2 assimilation. Their transcription depends on the activator protein CbbR. Structure-function relationships in the cloned chromosomal promoter region were analyzed by site-directed mutagenesis. PL was altered in its presumed hexameric −35 and/or −10 box or in the spacer region between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
10

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 34 publications
0
9
0
10
Order By: Relevance
“…Another mutant strain, H16G∆ cbbR , was constructed by deletion of cbbR on chromosome 2, encoding a common transcriptional activator for the two cbb operons. It has been reported that a cbbR -deleted strain of R. eutropha was incapable of growing autotrophically owing to insufficient induction of the cbb genes 26 . Indeed, qRT-PCR analysis demonstrated that expression levels of cbbL (encoding Rubisco large subunit), cbbP (encoding phosphoribulokinase) and cbbF (encoding fructose-1,6-bisphosphatase I/sedoheptulose-1,7-bisphosphatase) in H16G∆ cbbR incubated with glucose were approximately one-hundredth compared to those in the parent strain H16G ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another mutant strain, H16G∆ cbbR , was constructed by deletion of cbbR on chromosome 2, encoding a common transcriptional activator for the two cbb operons. It has been reported that a cbbR -deleted strain of R. eutropha was incapable of growing autotrophically owing to insufficient induction of the cbb genes 26 . Indeed, qRT-PCR analysis demonstrated that expression levels of cbbL (encoding Rubisco large subunit), cbbP (encoding phosphoribulokinase) and cbbF (encoding fructose-1,6-bisphosphatase I/sedoheptulose-1,7-bisphosphatase) in H16G∆ cbbR incubated with glucose were approximately one-hundredth compared to those in the parent strain H16G ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it encodes the Strep epitope downstream of the artificial cbb c -P L -M9 promoter (Fig. 2b), which directs high constitutive expression levels in R. eutropha (Jeffke et al, 1999). Restriction sites downstream of the strep-tag sequence facilitate the construction of fusion genes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The derivatives pGP1655 and pGP1656 of plasmid pBBR1MCS-3 were assembled in several steps. First, the cbb c -P L -M9 promoter was amplified by PCR using primers DK15/DK16 and plasmid pBKM9 (Jeffke et al, 1999) as the template. This DNA fragment was used to replace the XbaI-KpnI fragment of plasmid pGP788 K, resulting in plasmid pGP1651.…”
Section: Methodsmentioning
confidence: 99%
“…Regions of interest were amplified from PAK genomic DNA and ligated into a cloning vector. A section of the coding sequence was then deleted (and replaced by an antibiotic resistance cassette in some cases) and this inactivated operon was then cloned into the suicide plasmid pNHG1 (Jeffke et al ., 1999). To inactivate ccoNOQP ‐1, a 1554 bp BstB I to EcoR I fragment was replaced by a ΩGm r cassette to create strain Cco1.1 (Fig.…”
Section: Methodsmentioning
confidence: 99%